UMPSA and SWCorp Pahang collaborate to educate local community on compost production techniques using ‘Takakura’ method - Muhammad Nasrullah, Alias (UMPSA, 2024)
PEKAN, 1 August 2024 – A total of 30 villagers around Pekan, Pahang, participated in the Compost Fertiliser Production Workshop from food waste at UMPSA Pekan, organised by the Faculty of Manufacturing and Mechatronics Engineering Technology (FTKPM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) in collaboration with the Pahang Solid Waste Management and Public Cleansing Corporation (SWCorp).